Effect of blast on dry matter production, grain yield and yield components in upland rice - Prabhu, Anne Sitarama; Faria, Josias Corrêa de; Carvalho, José Ruy Porto de (Pesquisa Agropecuaria Brasileira, 2014)
The effect of leaf and panicle blast (Pyricularia oryzae Cav.) on dry matter production, plant height, 1,000 grain weight, percentage of unfilled grains, panicle weight and grain yield were compared in five early and nine medium duration cultivars under upland conditions. The reduction in plant height and loss in dry matter yield were significant in early maturing cultivars. The variation in 1,000 grain weight and percentage of unfilled grains was explained more by panicle blast than leaf blast. The effect was, however, greater in increasing the percentage of unfilled grains (19% to 58%) than 1,000 grain weight reduction (8% to 14%) both in early and medium maturing cultivars. The average yield loss during two years, for early varieties ranged from 15% to 38% and for medium duration ones from 37% to 44% when blast was partially controlled.
Keywords: Pyricularia oryzae; Oryzasativa; loss estimates